Coupling δ2H and δ18O biomarker results yields information on relative humidity and isotopic composition of precipitation ? a climate transect validation study - Tuthorn, M. (2015)
The hydrogen isotopic composition (δ 2H) of leaf waxes, especially of n-alkanes (δ 2Hn−alkanes), is increasingly used for paleohydrological and paleoclimate reconstructions. However, it is challenging to disentangle past changes in the isotopic composition of precipitation and changes in evapotranspirative enrichment of leaf water, which are both recorded in leaf wax δ 2H values. In order to overcome this limitation, Zech M. et al. (2013) proposed a coupled δ 2Hn−alkane–δ 18Osugar biomarker approach. This coupled approach allows for calculating (i) biomarker-based “reconstructed” δ 2H/δ18O values of leaf water (δ 2H/δ18Oleaf water), (ii) biomarker-based reconstructed deuterium excess (dexcess) of leaf water, which mainly reflects evapotranspirative enrichment and which can be used to reconstruct relative air humidity (RH) and (iii) biomarker-based reconstructed δ 2H/δ18Oprecipitation values. Here we present a climate transect validation study by coupling new results from δ 2H analyses of n-alkanes and fatty acids in topsoils along a climate transect in Argentina with previously measured δ 18O results obtained for plantderived sugars. Accordingly, both the reconstructed RH and δ 2H/δ18Oprecipitation values correlate highly significantly with actual RH and δ 2H/δ18Oprecipitation values. We conclude that compared to single δ 2Hn−alkane or δ 18Osugar records, the proposed coupled δ 2Hn−alkane–δ 18Osugar biomarker approach will allow more robust δ 2H/δ18Oprecipitation reconstructions in future paleoclimate research. Additionally, the proposed coupled δ 2Hn−alkane–δ 18Osugar biomarker approach allows for the establishment of a “paleohygrometer”, more specifically, the reconstruction of mean summer daytime RH changes/history